Ризики впровадження штучного інтелекту в сфери життя людини - Помелуйко, Д. А. (ХНУРЕ, 2020)
The topics of artificial intelligence and the security of intelligent technologies are highly relevant and important in the modern digital world. Artificial Intelligence is a variety of software and hardware technologies that can be applied in numerous ways for different applications. However, the development of artificial intelligence can raise problems and requires legal standards for the safe functionality of artificial intelligence systems.
Keywords: штучний інтелект; робот; соціальне управління